Implementing Smart Automation Solutions in Medium-Scale Industries Using SCADA Systems - Gbenga Olumide Omoegun; Evans Abiodun Sunday; Mmedo Anietie Essien; Odunayo Abosede Oluokun (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This study examines the strategic deployment of intelligent automation systems in medium-scale industrial environments, focusing on the integration of Supervisory Control and Data Acquisition (SCADA) architecture as a catalyst for operational transformation. The research sought to investigate how smart automation technologies, supported by Artificial Intelligence (AI), Machine Learning (ML), and the Industrial Internet of Things (IIoT), enhance real-time process control, efficiency, and sustainability. Using a conceptual and analytical approach grounded in contemporary industrial frameworks, the study synthesized multidisciplinary insights from automation engineering, data analytics, and systems management to develop a comprehensive understanding of how SCADA-based automation advances industrial performance. Findings reveal that the convergence of SCADA with AI-driven analytics and IoT infrastructures fosters intelligent decision-making, predictive maintenance, and efficient resource utilization across production networks. The study further establishes that while automation fosters transparency and productivity, medium-scale industries often face implementation challenges, including financial constraints, cybersecurity vulnerabilities, and insufficient technical expertise. The incorporation of robust cybersecurity protocols and adaptive governance mechanisms was found to be essential for ensuring secure and sustainable system integration. The paper concludes that SCADA systems form the foundation of digital transformation in medium-scale industries, enabling operational resilience and competitive advantage. It emphasizes the necessity of a phased, scalable approach to automation, one that harmonizes technological innovation with workforce readiness, data ethics, and sustainable practices. The study recommends policy-driven support, infrastructure investment, and cross-sector collaboration to promote equitable access to automation technologies and long-term industrial modernization. Through this synthesis, the research underscores the evolution of medium-scale industries toward intelligent, self-regulating, and ethically governed operational ecosystems.